Upgrading Financial Literacy of the Community and Entrepreneurs in the Face of Inflation through Writing and Publishing Articles on Kumparan - Hakiki, Moh. Saiful; Putra, Riyan Sisiawan; Adinugroho, Mukhtar (Indonesia Berdaya, 2023)
This community service activity discusses the importance of financial literacy in managing company finances effectively, especially in the face of inflation. In the era of globalization and rapid economic change, people and entrepreneurs are required to have adequate knowledge and skills in facing these financial challenges. Community service activities are explained as an effective method to improve their financial literacy in the face of inflation. The method of community service activities includes three concrete steps. First, the identification of financial literacy needs is carried out through a literature review to understand economic conditions, financial literacy information, and challenges faced by the public and entrepreneurs in facing inflation. Second, the writing and collection of previous articles and textbooks is carried out in a language that is easily understood by the general public and contains relevant information and workable solutions. Third, these articles are published in popular online media such as Kumparan to facilitate public access to information and knowledge about financial literacy. In the results and discussion section, financial literacy needs were identified based on the level of understanding of financial management policies, awareness of the importance of financial literacy, information and education needs, and availability of resources. Furthermore, it describes financial management policy steps that can be taken in dealing with inflation, such as financial risk identification, financial risk analysis, planning responses to risks, implementing these responses, and evaluating implementation results. The discussion also emphasized the importance of monitoring the company's financial performance through financial ratios. The closing of the article provides suggestions for further community service activities. Overall, this activity underscores the importance of financial literacy in the face of inflation and provides practical guidance for entrepreneurs and the public in managing company finances.